Adverse Childhood Experiences and Early Maladaptive Schemas as Predictors of Cyber Dating Abuse: An Actor-Partner Interdependence Mediation Model Approach - Celsi, Laura; Paleari, F. Giorgia; Fincham, Frank D. (Frontiers in Psychology, 2021)
The increasing role that new technologies play in intimate relationships has led to the emergence of a new form of couple violence, cyber dating abuse, especially among adolescents and young adults. Although this phenomenon has received increased attention, no research has investigated predictors of cyber dating abuse taking into account the interdependence of the two partners. The study examines adverse childhood experiences (abuse, neglect, and witnessed intimate partner violence) and early maladaptive schemas (emotional deprivation and abandonment) as possible predictors of young adults’ perpetrated and suffered cyber dating abuse. Adopting a dyadic approach, mediational models in which adverse childhood experiences were assumed to be related to individual and partner’s cyber dating abuse through individual early maladaptive schemas were tested. 134 couples completed online self-reports of the variables of interest, including a bidimensional measure of cyber dating abuse assessing pressure-aggression and control-monitoring. Actor-partner interdependence mediation model analyses were conducted. Results indicated that the emotional deprivation schema mediated the association between adverse childhood experiences and cyber dating abuse, whereas the abandonment schema did not. Specifically, more frequent experiences of emotional abuse and physical neglect during childhood were indirectly related to increased likelihood of perpetrating cyber dating pressure-aggression as well as of perpetrating and suffering cyber dating control-monitoring in both males and females. These associations were mediated by a stronger internalization of the emotional deprivation schema and were supported by both self-reported and partner-reported data. Also, a strong and direct association was found between childhood exposure to intimate partner violence by the opposite-sex parent and cyber dating pressure-aggression by females or control-monitoring by both males and females. These findings help to clarify the potential negative effects of specific adverse childhood experiences and early maladaptive schemas on the tendency to perpetrate and suffer cyber abuse in romantic relationships. The implications for prevention and treatment programs are noted and avenues for future research are described.